High-strength copper alloy strip for connector and preparation method of high-strength copper alloy strip

CN120400613APending Publication Date: 2025-08-01NINGBO XINGYE SHENGTAI GROUP +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510878883.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-27
Publication Date
2025-08-01

AI Technical Summary

Technical Problem

传统黄铜的力学性能和导电性逐渐无法满足一些中高端产品的需求

Benefits of technology

本发明提供的连接器用高强铜合金带材,在磷青铜合金‌的基础上组合添加了Fe和Ni元素,提高了P和Zn的含量,并显著降低了Sn的含量。该产品带材的抗拉强度为580~770MPa,断后延伸率A50≥3%,硬度HV170~240,导电率≥20%IACS,晶粒度≤0.015mm。可以在多点连接器、接插端子、插座等制造方面有效的替代锡磷青铜产品,实现材料降本。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a high-strength copper alloy strip for a connector and a preparation method of the high-strength copper alloy strip, and relates to the technical field of copper alloys. The high-strength copper alloy strip for the connector, provided by the invention, comprises the following components in percentage by mass: 85.0%-92.0% of Cu, 0.5%-1.0% of Ni, 0.3%-1.0% of Sn, 0.1%-0.2% of P, 0.1%-0.3% of Fe and the balance of Zn, the ratio of the total amount of substance of Fe and Ni to the amount of substance of P is greater than or equal to 4. According to the high-strength copper alloy strip for the connector, the tensile strength ranges from 580 MPa to 770 MPa, the percentage elongation after fracture A50 is larger than or equal to 3%, the hardness HV ranges from 170 to 240, the electric conductivity is larger than or equal to 20% IACS, and the grain size is smaller than or equal to 0.015 mm. And tin-phosphor bronze products can be effectively replaced in the manufacturing aspects of multi-point connectors, plugging terminals, sockets and the like, so that the cost of materials is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of copper alloys, and particularly relates to a high-strength copper alloy strip for connectors and a preparation method thereof. Background Art

[0002] Connectors are essential key components for electrical connection or signal transmission between circuit units and have been widely used in the fields of military, communication, automotive, consumer electronics, industry, etc. Common alloys on the market currently include brass, phosphor bronze, copper-nickel alloys, copper-chromium alloys, etc. Among them, brass is widely used due to its cost advantage and good processing performance. With the rapid development of fields such as consumer electronic devices, artificial intelligence, and new energy vehicles, electronic components are developing towards being thinner, lighter, and at the same time, the current-carrying capacity per unit cross-sectional area is also increasing, posing higher requirements for the comprehensive performance of copper alloys. The mechanical properties and electrical conductivity of traditional brass gradually cannot meet the requirements of some mid- to high-end products. Phosphor bronze, copper-nickel alloys, and copper-chromium alloys have relatively high comprehensive performance, but have the disadvantages of difficult processing and high cost.

[0003] In view of this, the present invention is specifically proposed. Summary of the Invention

[0004] The first object of the present invention is to provide a high-strength copper alloy strip for connectors to solve the above technical problems.

[0005] The second object of the present invention is to provide a preparation method for the above high-strength copper alloy strip for connectors.

[0006] In order to achieve the above objects, the following technical solutions are specifically adopted: In the first aspect, the present invention provides a high-strength copper alloy strip for connectors, which, by mass percentage, includes: Cu 85.0% - 92.0%, Ni 0.5% - 1.0%, Sn 0.3% - 1.0%, P 0.1% - 0.2%, Fe 0.1% - 0.3%, and the balance is Zn; The ratio of the total amount of substance of Fe and Ni to the amount of substance of P is greater than or equal to 4.

[0007] As a further technical solution, it further includes trace elements with a mass ratio of 0.1% - 0.8%; The trace elements are one or more of Si, Mn, Mg, Co, Cr, Ti, Zr, Al, or Pb.

[0008] In the second aspect, the present invention provides a preparation method for the above high-strength copper alloy strip for connectors, including the following steps: Ingredients are proportioned by mass percentage, and then melting, casting, hot rolling, online solution treatment, first cold rolling, continuous annealing, second cold rolling, first bell annealing, third cold rolling and second bell annealing are carried out in sequence to prepare a high-strength copper alloy strip for connectors.

[0009] As a further technical solution, the temperature of the melting is 1210~1230 °C; The temperature of the casting is 1200~1220 °C, the drawing casting speed is 60~90 mm / min, and the cooling water flow rate is 35~45 m 3 / h.

[0010] As a further technical solution, the starting rolling temperature of the hot rolling is 830~920 °C; the final rolling temperature of the hot rolling is 650 - 750 °C; the total processing rate of the hot rolling is 90%~95%.

[0011] As a further technical solution, the online solution treatment is to spray cooling water on the alloy material after hot rolling.

[0012] As a further technical solution, the total processing rate of the first cold rolling is 80%~85%; The total processing rate of the second cold rolling is 40%~70%; The total processing rate of the third cold rolling is 30%~60%.

[0013] As a further technical solution, the continuous annealing is carried out in a vertical continuous annealing furnace, the annealing temperature is 550~650 °C, and the annealing speed is 25~forty m / min.

[0014] As a further technical solution, the first bell annealing is carried out in a bell annealing furnace, the annealing temperature is 420~450 °C, and the holding time is 4~6 h.

[0015] As a further technical solution, the second bell annealing is carried out in a bell annealing furnace, the annealing temperature is 300~350 °C, and the holding time is 4~6 h.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The high-strength copper alloy strip for connectors provided by the present invention combines and adds Fe and Ni elements on the basis of a phosphor bronze alloy, increases the contents of P and Zn, and significantly reduces the content of Sn. The tensile strength of the strip of this product is 580~770 MPa, the elongation after fracture A50≥3%, the hardness HV170~240, the conductivity ≥20% IACS, and the grain size ≤0.015 mm. It can effectively replace tin phosphor bronze products in the manufacture of multi-point connectors, plug terminals, sockets, etc., and achieve cost reduction of materials. Detailed Embodiments

[0017] The embodiments of the present invention will be described in detail below in combination with the embodiments and examples. However, those skilled in the art will understand that the following embodiments and examples are only used to illustrate the present invention and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the scope of protection of the present invention. Those not specified in specific conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments not specified in the manufacturer are all conventional products that can be obtained through commercial purchase.

[0018] The mechanical properties and electrical conductivity of traditional brass can gradually no longer meet the requirements of some mid - to - high - end products. Phosphor bronze, copper - nickel alloys, and copper - chromium alloys have relatively high comprehensive properties, but they have the disadvantages of difficult processing and high costs. Aiming at the deficiencies of the prior art, the present invention provides a high - strength copper alloy strip for connectors, which mainly consists of Cu, Ni, Sn, P, Fe, and Zn. The content of Cu can be, for example, but not limited to, 85.0%, 88.0%, or 92.0%; the content of Ni can be, for example, but not limited to, 0.5%, 0.8%, or 1.0%; the content of Sn can be, for example, but not limited to, 0.3%, 0.7%, or 1.0%; the content of P can be, for example, but not limited to, 0.1%, 0.15%, or 0.2%; the content of Fe can be, for example, but not limited to, 0.1%, 0.2%, or 0.3%; and the ratio of the total amount of substance of Fe and Ni to the amount of substance of P is greater than or equal to 4.

[0019] In the present invention, Zn can be dissolved in the matrix to form an α - solid solution, causing lattice distortion and improving the elasticity and strength of the alloy. During the melting process, Zn can improve the fluidity of the melt and reduce the porosity defects during the casting process. If the content of Zn element is too low, the solution strengthening effect is not significant, and excessive addition of Zn will reduce the electrical conductivity of the alloy.

[0020] Ni has an atomic radius similar to that of Cu, will occupy the position of Cu atoms, and can form a solid solution in any proportion, improving the strength of the alloy. In addition, Ni can form Ni x Si y 、Ni x P y - based precipitation phases. The second - phase particles are dispersed in the matrix, which can effectively hinder the slip of dislocations and refine the grains. If the content of Ni is too low, the strengthening effect is not significant, and there is not enough Ni to combine with P, which will lead to excessive P and then reduce the electrical conductivity of the alloy. If the content of Ni is too high, it is easy to form coarse second - phase particles, which will affect the mechanical properties of the material and also reduce the conductivity.

[0021] Sn enhances the strength of the alloy through solid solution strengthening. This element has a significant work-hardening effect and can improve the corrosion resistance of copper alloys. If the content of Sn is too low, the strengthening effect is not obvious; if it is too high, it will cause great damage to the electrical conductivity.

[0022] P can form Ni x P y with Ni and Fe x P y precipitation phases, which hinder the movement of dislocations and grain boundaries, refine the grains, and improve the strength of the alloy. In addition, the element P has the functions of degassing and increasing the fluidity of the melt. If the content of P is too low, insufficient precipitation phases cannot be formed; if it is too high, it will have an adverse effect on the conductivity and is likely to cause hot rolling cracking.

[0023] Fe can form Fe x P y precipitates, which hinder the movement of dislocations and grain boundaries, refine the grains, and improve the strength of the alloy. If the content of Fe is too small, insufficient precipitation phases cannot be formed; if it is too much, agglomeration is likely to occur, reducing the mechanical properties.

[0024] Based on the functions of the above elements, the high-strength copper alloy strip for connectors provided by the present invention reduces the usage amount of Sn, thereby reducing the raw material cost and processing cost (Sn will increase the work-hardening rate of the strip, resulting in more processing passes. In addition, a higher content of Sn is likely to form inverse segregation in the ingot, requiring an additional homogenization annealing process). In addition, the solution of the present invention optimizes the composition of the alloy, and adds various elements such as Ni, P, and Fe in a certain proportion. These elements form Ni x P y and Fe x P y and other various precipitation phases in the alloy, which hinder the movement of dislocations and grain boundaries, thereby refining the grains and improving the strength of the alloy. A certain content of P has a deoxidation effect, which is beneficial to reducing ingot defects and improving the alloy properties.

[0025] In some alternative embodiments, it further includes trace elements with a mass ratio of 0.1% to 0.8%; The trace elements are one or more of Si, Mn, Mg, Co, Cr, Ti, Zr, Al, or Pb.

[0026] Minor addition of Si, Mn, Mg, Co, Cr, Ti, Zr, Al, and Pb can refine the grain size and improve the mechanical properties of the material. Excessive addition will reduce the electrical conductivity of the alloy, while less addition will result in insignificant strengthening effect. Among them, Cr preferentially precipitates at the grain boundaries during the melting and casting process, so it can achieve the effect of grain boundary strengthening and reduce the cracking phenomenon during the hot rolling process. In addition, Cr can also improve the corrosion resistance of copper alloys, but excessive addition of Cr will lead to the formation of coarse second phases. Si can form Ni x Si y , Co x Si y -based precipitation phases, which hinder the movement of dislocations and grain boundaries, refine the grain size, and improve the strength of the alloy.

[0027] In some preferred embodiments, the trace elements are Si, Co, and Cr; Preferably, the mass ratios of Si, Co, and Cr are 0.1%, 0.1%, and 0.1% respectively In some alternative embodiments, the thickness of the high-strength copper alloy strip for connectors is 0.1 - 0.3 mm, for example, it can be, but is not limited to, 0.1 mm, 0.2 mm, or 0.3 mm, and the width ≥ 580 mm.

[0028] In a second aspect, the present invention provides a method for preparing the above-mentioned high-strength copper alloy strip for connectors, including the following steps: Weigh the ingredients according to mass percentages, and then successively carry out melting, casting, hot rolling, online solution treatment, first cold rolling, continuous annealing, second cold rolling, first bell annealing, third cold rolling, and second bell annealing to prepare the high-strength copper alloy strip for connectors.

[0029] In the preparation method provided by the present invention, through hot rolling and online solution treatment, multiple elements such as Ni, P, and Fe are controlled to be fully dissolved in the matrix. Subsequently, multi-stage thermomechanical treatment (multiple cold rolling and annealing) is carried out. During the subsequent first rolling process, the processing residual heat generated by cold rolling can promote the partial precipitation of easily precipitated elements such as Ni, P, and Fe, generating Ni x P y , Fe x P y and other dispersed phases. During the subsequent continuous annealing process, these precipitated Ni x P y , Fe x P yEqui-dispersed phases can provide recrystallization nucleation sites and delay the grain boundary migration process, facilitating grain refinement. During the subsequent secondary cold rolling process, these fine precipitates will accelerate the multiplication of dislocations, forming more nucleation sites for the subsequent first bell annealing, while reducing the activation energy of nucleation and lowering the peak aging temperature. The reduction of the aging temperature and the large number of fine and dispersed precipitates can prevent obvious growth during the further precipitation of precipitates in the first bell annealing process. The effects of the subsequent third cold rolling and second bell annealing are similar to those of the secondary cold rolling and first bell annealing, further promoting the precipitation of solid solution elements and improving the electrical and mechanical properties of the alloy. The properties and thickness specifications of the strip can be further adjusted by increasing the number of cold rolling and bell annealing times.

[0030] In some alternative embodiments, the melting temperature can be, for example, but not limited to, 1210 °C, 1220 °C or 1230 °C; The casting temperature can be, for example, but not limited to, 1200 °C, 1210 °C or 1220 °C, the casting speed can be, for example, but not limited to, 60 mm / min, 80 mm / min or 90 mm / min, and the cooling water flow rate can be, for example, but not limited to, 35 m 3 / h, 40 m 3 / h or 45 m 3 / h.

[0031] In some alternative embodiments, a walking beam furnace is used to heat the ingot, with a temperature range of 860 - 950 °C and a holding time of 6 - 8 h, followed by hot rolling.

[0032] In some alternative embodiments, the starting rolling temperature of the hot rolling can be, for example, but not limited to, 830 °C, 880 °C or 920 °C; the final rolling temperature of the hot rolling can be, for example, but not limited to, 650 °C, 700 °C or 750 °C; the total reduction ratio of the hot rolling can be, for example, but not limited to, 90%, 93% or 95%.

[0033] In some alternative embodiments, the online solution treatment is to spray cooling water on the hot-rolled alloy material.

[0034] In some alternative embodiments, facing is performed after the online solution treatment, and the specific operation method is not limited, and a method well-known to those skilled in the art can be used.

[0035] In some alternative embodiments, the total reduction ratio of the first cold rolling can be, for example, but not limited to, 80%, 83% or 85%; the number of cold rolling passes of the first cold rolling is 7 - 9.

[0036] In some alternative embodiments, the total reduction ratio of the second cold rolling may be, for example, but not limited to, 40%, 50% or 70%; the number of cold rolling passes for the second cold rolling is 5 to 7.

[0037] In some alternative embodiments, the total reduction ratio of the third cold rolling may be, for example, but not limited to, 30%, 40% or 60%; after the third cold rolling, a strip rolled to the finished product specification thickness is obtained.

[0038] In some alternative embodiments, the continuous annealing is carried out in a vertical continuous annealing furnace. The annealing temperature may be, for example, but not limited to, 550°C, 600°C or 650°C, and the annealing speed may be, for example, but not limited to, 25 m / min, 30 m / min or 40 m / min. The alloy recrystallizes through continuous annealing to refine the grains.

[0039] In some alternative embodiments, the first bell annealing is carried out in a bell annealing furnace to promote the precipitation of solid solution elements and provide the electrical conductivity of the alloy. The annealing temperature may be, for example, but not limited to, 420°C, 430°C or 450°C, and the holding time may be, for example, but not limited to, 4 h, 5 h or 6 h; annealing is carried out in a 75% H2 + 25% N2 atmosphere, and the cooling method is furnace cooling.

[0040] In some alternative embodiments, the second bell annealing is carried out in a bell annealing furnace to promote the precipitation of solid solution elements and regulate the electrical conductivity of the alloy. The annealing temperature may be, for example, but not limited to, 300°C, 330°C or 350°C, and the holding time may be, for example, but not limited to, 4 h, 5 h or 6 h; annealing is carried out in a 75% H2 + 25% N2 atmosphere, and the cooling method is furnace cooling.

[0041] The present invention will be further described below through specific examples and comparative examples. However, it should be understood that these examples are only for more detailed description and should not be construed as limiting the present invention in any way.

[0042] Example 1 A high-strength copper alloy strip for connectors, the elemental composition is shown in Table 1. By mass percentage, it includes Cu: 92.0%, Ni: 0.5%, Sn: 0.3%, P: 0.1%, Fe: 0.1%, Si: 0.1%, and the balance is zinc and unavoidable impurities.

[0043] The preparation method is as follows: a. Weigh the raw materials according to the alloy composition ratio, and after mixing, carry out feeding, melting and casting in sequence, b. Hot rolling and online solution treatment, c. Facing, d. First cold rolling, e. Continuous annealing, f. Second cold rolling, g. First bell annealing, h. Third cold rolling, i. Second bell annealing.

[0044] In step a, a non-vacuum intermediate frequency induction furnace is used for melting and casting. Electrolytic copper, zinc ingots, nickel plates, pure tin, copper-silicon master alloy, copper-iron master alloy, and copper-phosphorus master alloy are added to the furnace. The temperature is raised to 1200 - 1220 °C. After the melt is completely melted, it is poured into a holding furnace and stirred evenly. The casting temperature is controlled at 1180 - 1200 °C, and after holding for 10 min, casting is carried out. The initial drawing speed is 65 ± 5 mm / min, the normal drawing speed is 85 ± 5 mm / min, and the normal cooling water flow rate is 35 - 45 m 3 / h.

[0045] In step b, the above alloy ingot is heated in a walking beam type furnace at a temperature range of 860 °C for 8 h, hot worked and deformed at 830 °C with a total reduction rate of 90%, and the final rolling temperature is 650 °C. Subsequently, online solution treatment is achieved by using water-cooled spraying.

[0046] In step d, the milled strip is cold rolled once with a cold rolling reduction rate of 80% and undergoes 7 passes of rolling to obtain the target thickness.

[0047] In step e, the strip after the first cold rolling is placed in a vertical continuous annealing furnace for continuous annealing treatment. The annealing temperature is 550 °C and the annealing speed is 25 m / min.

[0048] In step f, the alloy sheet after recrystallization annealing is cold rolled twice with a cold rolling reduction rate of 40% and undergoes 7 passes of rolling to obtain the target thickness.

[0049] In step g, the alloy strip after the second cold rolling is annealed in a bell-type annealing furnace. The heating-up time is 4 h, the temperature is 420 °C, the holding time is 6 h, and annealing is carried out in an atmosphere of 75% H2 + 25% N2, and the cooling method is furnace cooling.

[0050] In step h, the alloy sheet after annealing treatment is cold rolled three times with a rolling reduction rate of 30% and is rolled in multiple passes to the finished product specification thickness.

[0051] In step i, the alloy strip after the third cold rolling is annealed at low temperature in a bell-type annealing furnace. The heating-up time is 4 h, the temperature is 300 °C, the holding time is 6 h, and annealing is carried out in an atmosphere of 75% H2 + 25% N2, and the cooling method is furnace cooling.

[0052] Example 2: A high-strength copper alloy strip for connectors, the elemental composition is shown in Table 1. By mass percentage, it includes Cu: 90.0%, Ni: 0.6%, Sn: 0.4%, P: 0.1%, Fe: 0.15%, Mg: 0.1%, Ti: 0.2%, and the balance is zinc and unavoidable impurities.

[0053] The preparation method is as follows: a. Weigh the raw materials according to the alloy composition ratio, and after mixing, carry out feeding, melting and casting in sequence. b. Hot rolling and online solution treatment. c. Surface milling. d. First cold rolling. e. Continuous annealing. f. Second cold rolling. g. First bell annealing. h. Third cold rolling. i. Second bell annealing.

[0054] In step a, a non-vacuum medium frequency induction furnace is used for melting and casting. Electrolytic copper, zinc ingots, nickel plates, pure tin, copper-silicon master alloy, copper-iron master alloy, copper-phosphorus master alloy, pure magnesium, and titanium sponge are added to the furnace. The temperature is raised to 1200 - 1220 °C. After the melt is completely melted, it is poured into a holding furnace and stirred evenly. The casting temperature is controlled at 1180 - 1200 °C, and after holding for 10 min, casting is carried out. The initial drawing speed is 65 ± 5 mm / min, the normal drawing speed is 85 ± 5 mm / min, and the normal cooling water flow rate is 35 - 45 m 3 / h.

[0055] In step b, the above alloy ingot is heated in a walking beam type furnace. The temperature range is 950 °C, and the holding time is 6 h. Hot working deformation is carried out at 920 °C, the total processing rate is 95%, the final rolling temperature is 750 °C, and then water-cooled spraying is used to achieve the online solution treatment effect.

[0056] In step d, the surface-milled strip is subjected to first cold rolling. The cold rolling processing rate is 85%, and it undergoes 9 passes of rolling to obtain the target thickness.

[0057] In step e, the strip after first cold rolling is placed in a vertical continuous annealing furnace for continuous annealing treatment. The annealing temperature is 650 °C, and the annealing speed is 40 m / min.

[0058] In step f, the alloy sheet after recrystallization annealing is subjected to second cold rolling. The cold rolling processing rate is 70%, and it undergoes 9 passes of rolling to obtain the target thickness.

[0059] In step g, the alloy strip after second cold rolling is placed in a bell-type annealing furnace for annealing treatment. The heating-up time is 4 h, the temperature is 450 °C, the holding time is 4 h, and annealing is carried out in an atmosphere of 75% H2 + 25% N2. The cooling method is furnace cooling.

[0060] In step h, the alloy sheet after annealing treatment is subjected to third cold rolling. The rolling processing rate is 30 - 60%, and it is rolled in multiple passes to the finished product specification thickness.

[0061] In step i, the alloy strip after third cold rolling is placed in a bell-type annealing furnace for low-temperature annealing treatment. The heating-up time is 4 h, the temperature is 350 °C, the holding time is 4 h, and annealing is carried out in an atmosphere of 75% H2 + 25% N2. The cooling method is furnace cooling.

[0062] Example 3: A high-strength copper alloy strip for connectors, with the elemental composition shown in Table 1. By mass percentage, it includes Cu: 88.0%, Ni: 0.7%, Sn: 0.6%, P: 0.15, Fe: 0.2, Zr: 0.2, Al: 0.2, and the balance is zinc and inevitable impurities.

[0063] The preparation method is as follows: a. Weigh the raw materials according to the alloy composition ratio, and after mixing, carry out feeding, melting, and casting in sequence. b. Hot rolling and online solution treatment. c. Surface milling. d. First cold rolling. e. Continuous annealing. f. Second cold rolling. g. First bell annealing. h. Third cold rolling. i. Second bell annealing. j. Fourth cold rolling. k. Third bell annealing.

[0064] In step a, a non-vacuum medium-frequency induction furnace is used for melting and casting. Electrolytic copper, zinc ingots, nickel plates, pure tin, copper-silicon master alloy, copper-iron master alloy, copper-phosphorus master alloy, copper-chromium master alloy, and pure aluminum are added to the furnace. The temperature is raised to 1200 - 1220 °C. After the melt is completely melted, the melt is poured into a holding furnace and stirred evenly. The casting temperature is controlled at 1180 - 1200 °C, and it is poured after holding for 10 minutes. The initial drawing speed is 65 ± 5 mm / min, the normal drawing speed is 85 ± 5 mm / min, and the normal cooling water flow rate is 35 - 45 m 3 / h.

[0065] In step b, the above alloy ingot is heated in a walking beam furnace, the temperature range is 900 °C, the holding time is 7 h, hot working deformation is carried out at a temperature of 870 °C, the total processing rate is 92%, the final rolling temperature is 710 °C, and then water-cooling spraying is used to achieve the online solution effect.

[0066] In step d, the surface-milled strip is subjected to first cold rolling, the cold rolling processing rate is 82%, and it undergoes 8 passes of rolling to obtain the target thickness.

[0067] In step e, the strip after first cold rolling is placed in a vertical continuous annealing furnace for continuous annealing treatment. The annealing temperature is 600 °C, and the annealing speed is 30 m / min.

[0068] In step f, the alloy sheet after recrystallization annealing is subjected to second cold rolling, the cold rolling processing rate is 50%, and it undergoes 8 passes of rolling to obtain the target thickness.

[0069] In step g, the alloy strip after second cold rolling is annealed in a bell-type annealing furnace. The heating-up time is 4 h, the temperature is 430 °C, the holding time is 5 h, and annealing is carried out in an atmosphere of 75% H2 + 25% N2. The cooling method is furnace cooling.

[0070] In step h, the annealed alloy sheet is cold-rolled three times with a rolling reduction of 40% and undergoes 7 passes of rolling to obtain the target thickness.

[0071] In step i, the alloy strip after three cold-rollings is annealed in a bell-type annealing furnace with a heating-up time of 4 h, a temperature of 420 °C, a holding time of 5 h, and an annealing atmosphere of 75% H2 + 25% N2, and the cooling method is furnace cooling.

[0072] In step j, the annealed alloy sheet is cold-rolled four times with a rolling reduction of 30 - 60% and is multi-pass rolled to the finished product specification thickness.

[0073] In step k, the alloy strip after three cold-rollings is low-temperature annealed in a bell-type annealing furnace with a heating-up time of 4 h, a temperature of 320 °C, a holding time of 5 h, and an annealing atmosphere of 75% H2 + 25% N2, and the cooling method is furnace cooling.

[0074] Example 4: The difference from Example 1 lies in the different elemental compositions, as shown in Table 1.

[0075] Example 5: The difference from Example 1 lies in the different elemental compositions, as shown in Table 1.

[0076] Example 6: The difference from Example 1 is that it does not contain silicon element, and the elemental composition is shown in Table 1.

[0077] Example 7: The difference from Example 1 is that Si: 0.1, Co: 0.1, and Cr: 0.1 are added, and the elemental composition is shown in Table 1.

[0078] Example 8: The difference from Example 7 lies in the elemental composition shown in Table 1.

[0079] Example 9: The difference from Example 7 lies in the elemental composition shown in Table 1.

[0080] Example 10: The difference from Example 7 lies in the elemental composition shown in Table 1.

[0081] Comparative Example 1: The difference from Example 1 is that the content of Cu is too high, and the elemental composition is shown in Table 1.

[0082] Comparative Example 2: The difference from Example 1 is that the content of Ni is too low, and the elemental composition is shown in Table 1.

[0083] Comparative Example 3: The difference from Example 1 is that the content of Sn is too small, and the elemental composition is shown in Table 1.

[0084] Comparative Example 4: The difference from Example 1 is that the content of P is too small, and the elemental composition is shown in Table 1.

[0085] Comparative Example 5: The difference from Example 1 is that the content of Fe is too small, and the elemental composition is shown in Table 1.

[0086] Comparative Example 6: The difference from Example 1 is that the total addition amount of Si, Mn, Mg, Co, Cr, Ti, Zr, Al, and Pb is less than 0.1%, and the elemental composition is shown in Table 1.

[0087] Comparative Example 7: The difference from Example 1 is that (Fe + Ni) / P < 4, and the elemental composition is shown in Table 1.

[0088] Comparative Example 8: The difference from Example 5 is that the content of Cu is too small, and the elemental composition is shown in Table 1.

[0089] Comparative Example 9: The difference from Example 5 is that the content of Ni is excessive, and the elemental composition is shown in Table 1.

[0090] Comparative Example 10: The difference from Example 5 is that the content of Sn is excessive, and the elemental composition is shown in Table 1.

[0091] Comparative Example 11: The difference from Example 5 is that the content of P is excessive, and the elemental composition is shown in Table 1.

[0092] Comparative Example 12: The difference from Example 5 is that the content of Fe is excessive, and the elemental composition is shown in Table 1.

[0093] Comparative Example 13: The difference from Example 5 is that the addition amounts of Mn, Mg, Co, Cr, Ti, Zr, Al, and Pb are greater than 0.8%, and the elemental composition is shown in Table 1.

[0094] Comparative Example 14: The difference from Example 5 is that the online solution and water cooling spray processes were not used during the hot rolling process.

[0095] Table  1 Alloy Composition Formulas of Examples and Comparative Examples 。

[0096] The properties of the strip materials in the examples and comparative examples were detected respectively, and the results are shown in Table 2.

[0097] Table 2 Performance test results of examples and comparative examples 。

[0098] Comparing the examples with the comparative examples, it can be seen that the properties of the alloy strip in Example 1 are better than those in the comparative examples, indicating that better properties can be achieved only when the composition of each element is within the scope of the present invention.

[0099] Comparing Comparative Example 7 with Examples 8-10, it can be seen that the properties of the alloy strip in Example 7 are better than those in Examples 8-10, indicating that for the alloy of the present invention, there is a synergistic effect among the trace elements Si, Co and Cr, and the alloy properties can be further improved through cooperation.

[0100] Finally, it should be noted that the above examples are only used to illustrate the technical solutions of the present invention, rather than to limit them; although the present invention has been described in detail with reference to the foregoing examples, those of ordinary skill in the art should understand that they can still modify the technical solutions recorded in the foregoing examples, or perform equivalent replacements on some or all of the technical features; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A high-strength copper alloy strip for connectors, characterized in that, By mass percentage, it includes: Cu 85.0% - 92.0%, Ni 0.5% - 1.0%, Sn 0.3% - 1.0%, P 0.1% - 0.2%, Fe 0.1% - 0.3%, and the balance is Zn; The ratio of the total amount of substance of Fe and Ni to the amount of substance of P is greater than or equal to 4.

2. The high-strength copper alloy strip for connectors according to claim 1, wherein It also includes trace elements with a mass fraction of 0.1% - 0.8%; The trace elements are one or more of Si, Mn, Mg, Co, Cr, Ti, Zr, Al, or Pb.

3. The preparation method of the high-strength copper alloy strip for connectors according to claim 1 or 2, characterized in that, It includes the following steps: Weigh the ingredients according to the mass percentage, and then successively carry out melting, casting, hot rolling, online solution treatment, first cold rolling, continuous annealing, second cold rolling, first bell annealing, third cold rolling, and second bell annealing to prepare a high-strength copper alloy strip for connectors.

4. The preparation method according to claim 3, characterized in that, The temperature of the melting is 1210 - 1230 °C; The temperature of the casting is 1200~1220 °C, the drawing speed is 60~90 mm / min, and the cooling water flow rate is 35~45 m 3 / h.

5. The preparation method according to claim 3, characterized in that, The starting rolling temperature of the hot rolling is 830 - 920 °C; the final rolling temperature of the hot rolling is 650 - 750 °C; the total reduction ratio of the hot rolling is 90% - 95%.

6. The preparation method according to claim 3, characterized in that, The online solution treatment is to spray cooling water on the hot-rolled alloy material.

7. The preparation method according to claim 3, characterized in that, The total reduction ratio of the first cold rolling is 80% - 85%; The total reduction ratio of the second cold rolling is 40% - 70%; The total reduction ratio of the third cold rolling is 30% - 60%.

8. The preparation method according to claim 3, wherein The continuous annealing is carried out in a vertical continuous annealing furnace, the annealing temperature is 550 - 650 °C, and the annealing speed is 25 - 40 m / min.

9. The preparation method according to claim 3, wherein The first bell annealing is carried out in a bell annealing furnace, the annealing temperature is 420 - 450 °C, and the holding time is 4 - 6 h.

10. The preparation method according to claim 3, characterized in that, The second bell annealing is carried out in a bell annealing furnace, the annealing temperature is 300 - 350 °C, and the holding time is 4 - 6 h.